Heutagogical Approach in Professional Development for Teachers in Indonesian Madrasah: Fostering Autonomy and Innovative Teaching Practices - Abdul Muhid; Ahmad Yusuf; Ali Ridho (MUMTAZ : Jurnal Pendidikan Agama Islam, 2025)
This study aims to explore the implementation of heutagogy in teacher professional development in Indonesian madrasah using social media platforms as a learning tool. The main question addressed is how the heutagogical approach can enhance learning autonomy and promote teaching innovation among madrasah teachers. The study utilizes a Design-Based Research (DBR) approach to develop and test a professional development model based on heutagogy. The findings show that the implementation of this approach successfully increased teacher autonomy, fostered more innovative teaching practices, and facilitated collaboration through social media. This research makes a significant contribution in understanding how heutagogical approaches can improve the quality of teacher professional development in the digital age.